PENGELOLAAN ARSIP DINAMIS DI DINAS PARIWISATA DAERAH DAERAH ISTIMEWA YOGYAKARTA - , IKA AFIYANTI; , Dra. Eny Kusumindarti W ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The Final Report on the theme of records management in Dinas Pariwisata Daerah Daerah Istimewa Yogyakarta described the records management. The things you need to know from this administration were what archives were managed, how the records condition and records center systems. The records management were starting from the management of mailhandling filing system and records retrieval. The records management was also carried out for non correspondence records. The methods used to prepare this final report were observation, interviews, and literature study. The observation method was done by implementing direct practice in the field. The second method of collecting data was the interview method by asking questions for the officers who handles the records. The questions proposed relate to the records management of the Dinas Pariwisata Daerah Daerah Istimewa Yogyakarta. The last method was the method of literature study that collected data sourced from books or library materials on the records management. The conclusions from the study in Dinas Pariwisata Daerah Daerah Istimewa Yogyakarta showed the filing system that has been done regularly, it indicate a good Records Management records was more regularly after the filing. Facilities and infrastructure available was fully utilized but need the records center for housing of the inactive records that would be adequate to maintain the physical safety and records information.